Age-Related Mitochondrial Alterations Contribute to Myocardial Responses During Sepsis - Jiayue Du; Qing Yu; Olufisayo E. Anjorin; Meijing Wang (Cells)
Sepsis-induced myocardial injury is age-related and leads to increased mortality. Considering the importance of mitochondrial dysfunction in cardiac impairment, we aimed to investigate whether aging exacerbates the cardiac mitochondrial metabolic response to inflammation, thus leading to increased cardiac dysfunction in the elderly. Cecal ligation and puncture (CLP) was conducted in young adult (12–18 weeks) and aged (19–21 months) male C57BL/6 mice. Cardiac function was detected 20 h post-CLP. Additionally, cardiomyocytes isolated from young adult and aged male mice were used for assessments of mitochondrial respiratory function +/– TNFα or LPS. Protein levels of oxidative phosphorylation (OXPHOS), NADPH oxidase (NOX)2, NOX4, phosphor-STAT3 and STAT3 were determined in mouse hearts 24 h post-CLP and in cardiomyocytes following inflammatory stimuli. CLP significantly reduced cardiac contractility in both young and aged mice, with a higher incidence and greater severity of cardiac functional depression in the older group. Mitochondrial respiratory capacity was decreased in cardiomyocytes derived from aged mice, with increased susceptible to inflammatory toxic effects compared to those from young adult mice. The age-dependent changes were observed in myocardial OXPHOS complexes and NOX4. Importantly, CLP led to a significant increase in OXPHOS protein levels in the hearts of older mice, suggesting a possible compensatory response to decreased mitochondrial metabolic function and a greater potential for reactive oxygen species (ROS) generation. Our findings highlight that the response of aging-impaired mitochondria to inflammation may underlie the worsened cardiac functional depression in the aged group during sepsis.